The question concerning Technology and the technification of politics: : Heidegger and the question of dwelling - Villalobos Ruminott, Sergio (2023)
In the following pages we present the most important dimensions of the Heideggerian approach to the question of technology, to show its relevance and its relationship with contemporary developments related to the problem of original technicity and the so-called symbolic misery of contemporary post-industrial societies. For this purpose, we stop at this formulation emphasizing its scope in the field of politics and aesthetics, under the assumption that a modern image of technology coincides with a subjective and aesthetic image of art and with a permanent process of technification of politics supplied, in turn, by notions such as hegemony, will to power and domination. We conclude by returning to the question of dwelling raised by Heidegger as an exemplary instance of his thought.